Characterization of Contrasting Soybean Genotypes for Seed Longevity Using SSR Markers - BHARAMARAJ BADIGER; RAVI HUNJE; DP BIRADAR; NK BIRADAR PATIL; VILAS TONAPI (Seed Research, 2026)
In Soybean [Glycine max (L.) Merrill], seed storability is a major problem and identifying the genotypes with good storability as well as the DNA marker associated with seed storability will help in Markers Assisted Selection (MAS) programme targeted for breeding soybean genotype with better seed storability. In this study, six genotypes of soybean, varying in storability, were characterized using 14 SSR markers that were reported to be linked or associated with seed longevity. Out of 14 primers screened, the primers Satt 285, Satt 316, Satt 434 and Satt 538 gave distinct banding pattern among the good and poor storers. They produced the allele of size range from 184 bp in genotypes having poor seed longevity and the allele of size 235 bp for those genotypes having good seed longevity.